Diseño de un sistema de control para el monitoreo y seguimiento de fallas eléctricas en la subestación de la empresa FENOCO ubicada en Fundación – Magdalena - Cañizares Maestre, Deivis Saul (Universidad Antonio Nariño, 2022)
This work is aimed at designing a control system for the monitoring and follow-up of the electrical faults presented in the substation of the FENOCO company, located in Fundacion - Magdalena, based on the statistics of the recurring faults presented in the electrical system of the substation, with the purpose of making a diagnosis of the current situation of the system. Next, a checklist is applied to identify the correct operation of the electrical system and, in turn, observe the behavior of the electrical system in the event of faults that may arise. Then based on the above, the control system variables were defined to develop the substation monitoring system, which is designed with the Labview tool, to graphically visualize the system. Finally, a cost / benefit analysis of the system is carried out for the implementation of the proposed improvements to the system